(untitled) (Revista Educação, Artes e Inclusão, 2025)
Initial Teacher Educational (ITE) programs are expected to expand concepts and knowledge about teaching, especially when it includes practices in real schools, dealing with diverse students. During their professional career, many teachers mention that they were not properly prepared, during their undergraduate studies, to work in an inclusive way with disable students. The present work intends to reflect about the experience of two undergraduates in the context of an Initial Teacher Educational program, who were in contact with autistic students. We investigate, through autobiographical narratives, the importance of early contact with disable students, for developing teachers aligned with the perspective of inclusive education especially considering a panorama of increased diagnoses and enrollment of disable students, in regular classes. In this investigation we highlight (i) the presence of “not knowing” and “not doing” as a crucial part of the performance and training of teachers; (ii) the need for everyone’s willing to build and cross bridges between expectations and realities; (iii) the need for reception teachers in ITEs and teacher’s initiation, establishing a safe and supervised start.